Professional social support levels that physical education teachers perceive in educational institutions in Turkey - Karakaya, Yunus Emre; Hacicafero?lu, Serkan; Kilinç, Hasan Hüseydn (Editura Universitatea din Pitesti, 2014)
The aim of this study is to determine physical education teachers' perception of professional social support level in their educational institutions in Turkey. The sample group of the study consists of 220 physical education teachers from different educational institutions. To be able to obtain views of the sample group "Teacher Professional Social Support Scale" developed by Kaner (2007) was used. The data obtained was analyzed through the SPSS package programme. As a result of the analysis, some differences found with regard to variables of the service in the institution and number of the students at the "Management Support" subcomponent. Some differences found in terms of variables of gender, education level and number of the students in the institutions at the "Colleague Support" sub-component. Some differences found with regard to variables of school, education level, and year of service in the institution at the "Family Support" sub-component. Also some differences found at the "Effective Teaching Support" sub-component in terms of variables of education level and year of service in the institution. No significant differences found in terms of variables at the "Student Support" sub-component. Finally, effects of physical education teachers' perception of the social support on their professional development shouldn't be ignored when planning their career development in educational institutions. Some studies that will increase pyhsical education teachers' perception of social support should be done by educational institutions. © JPES.
Keywords: Educational institutions; Physical education teachers; Social support level; Turkey